Financial Sector Reforms in Eight Countries : Issues and Results - Galbis, Vicente (IMF Working Papers; Working Paper, 1995)
This paper examines financial sector reforms in eight developing countries--Argentina, Bulgaria, Ecuador, Egypt, India, Kenya, Tanzania, and Uganda--and derives general lessons from their experience. The paper reviews the initial situation of these countries; describes the financial sector (and related) reforms carried out, including sequencing issues, and points out the unresolved questions; and examines the effects of reforms on monetary control and financial development, investment and growth and the efficiency of financial intermediation. The main recommendations are the need to persevere with macroeconomic stabilization through indirect monetary policy instruments, and the need to substantially strengthen prudential regulation and supervision and restructure and privatize or liquidate ailing financial institutions.